Quantifying nitrous oxide production rates from nitrification and denitrification under various moisture conditions in agricultural soils: Laboratory study and literature synthesis - Wang, Hui; Yan, Zhifeng; Ju, Xiaotang; Song, Xiaotong; Zhang, Jinbo; Li, Siliang; Zhu-Barker, Xia (Frontiers in Microbiology, 2023)
Biogenic nitrous oxide (N2O) from nitrification and denitrification in agricultural soils is a major source of N2O in the atmosphere, and its flux changes significantly with soil moisture condition. However, the quantitative relationship between N2O production from different pathways (i.e., nitrification vs. denitrification) and soil moisture content remains elusive, limiting our ability of predicting future agricultural N2O emissions under changing environment. This study quantified N2O production rates from nitrification and denitrification under various soil moisture conditions using laboratory incubation combined with literature synthesis. 15N labeling approach was used to differentiate the N2O production from nitrification and denitrification under eight different soil moisture contents in the laboratory study, while 80 groups of data from 17 studies across global agricultural soils were collected in the literature synthesis. Results showed that as soil moisture increased, N2O production rates of nitrification and denitrification first increased and then decreased, with the peak rates occurring between 80% and 95% WFPS. By contrast, the dominant N2O production pathway switched from nitrification to denitrification between 60% and 70% WFPS. Furthermore, the synthetic data elucidated that moisture content was the major driver controlling the relative contributions of nitrification and denitrification to N2O production, while NH4+ and NO3- concentrations mainly determined the N2O production rates from each pathway. The moisture treatments with broad contents and narrow gradient were required to capture the comprehensive response of soil N2O production rate to moisture change, and the response is essential for accurately predicting N2O emission from agricultural soils under climate change scenarios.